2017
DOI: 10.22161/ijeab/2.6.62
|View full text |Cite
|
Sign up to set email alerts
|

Pre-sowing Treatment Enhanced Germination and Vigour of True Shallot (Allium cepa var. aggregatum) Seeds

Abstract: The objective of this research was to sudy the effects of pre-sowing treatments to enhance germination, growth and transplanting of true shallot seeds. The experiment was conducted in the glasshouse at Tangtu village, Badung regency from August until November 2017. Germination experiment was carried out in petridishes, while that for seedling vigour and growth experiment was done in plastic pots containing sand and top soil mixture. Both experiments were designed as complete randomized design with eight concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, the seed vigour can be improved through seed invigoration, i.e., by soaking the seeds in KNO 3 , PEG 6000 (Castañares, Bouzo 2018), GA 3 , ZnSO 4 and other osmotic solutions prior to planting (Kharat et al 2022). Research has shown that seed invigoration increases germination and the seedling establishment of onion seeds as compared to those of seed bulb crops, thereby ensuring uniformity and a specific growth rate (Mirabi, Hasanabadi 2012;Agung, Diara 2017). Seed invigoration has been proved to speed up germination and can be used to speed up the radicle emergence (RE) and reduce the mean germination time (Castañares, Bouzo 2018).…”
Section: Methodsmentioning
confidence: 99%
“…However, the seed vigour can be improved through seed invigoration, i.e., by soaking the seeds in KNO 3 , PEG 6000 (Castañares, Bouzo 2018), GA 3 , ZnSO 4 and other osmotic solutions prior to planting (Kharat et al 2022). Research has shown that seed invigoration increases germination and the seedling establishment of onion seeds as compared to those of seed bulb crops, thereby ensuring uniformity and a specific growth rate (Mirabi, Hasanabadi 2012;Agung, Diara 2017). Seed invigoration has been proved to speed up germination and can be used to speed up the radicle emergence (RE) and reduce the mean germination time (Castañares, Bouzo 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This means that the process of producing bulbs takes longer than with seed bulb crops, as they must be burried in the ground. Efforts must be made to extend seed germination and accelerate seedling establishment in order to shorten the time spent in the nursery (Agung & Diara, 2017). The hard structure of seeds prevents roots and spots from growing as well as oxygen and water from penetrating the seed coat.…”
Section: Introductionmentioning
confidence: 99%